2020
DOI: 10.1259/dmfr.20200039
|View full text |Cite
|
Sign up to set email alerts
|

Influence of windowing and metal artefact reduction algorithms on the volumetric dimensions of five different high-density materials: a cone-beam CT study

Abstract: Objective: To assess the influence of windowing and metal artefact reduction (MAR) algorithms on the volumetric dimensions of high-density materials using two CBCT systems. Methods: Four cylinders of amalgam, cobalt-chromium, gutta-percha, titanium and zirconium, were manufactured and their physical volumes (PV) were measured. A polymethyl methacrylate phantom containing the cylinders was submitted to CBCT acquisitions with Picasso Trio and OP300 units with their MAR enabled and disabled. The tomographic volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Artifacts are visualized structures formed in the image through the data reconstruction process that do not represent the subject being studied [ 1 , 7 ]. Factors involved in inducing the artifacts can be classified as follows: 1) artifacts caused by the physical structure of the CBCT system, such as the mathematical format used in the 3-dimensional reconstruction, 2) artifacts related to the image acquisition, such as patient movement, exposure settings including milliamperage (mA) and peak kilovoltage (kVp), and presence of high-density elements [ 5 , 8 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Artifacts are visualized structures formed in the image through the data reconstruction process that do not represent the subject being studied [ 1 , 7 ]. Factors involved in inducing the artifacts can be classified as follows: 1) artifacts caused by the physical structure of the CBCT system, such as the mathematical format used in the 3-dimensional reconstruction, 2) artifacts related to the image acquisition, such as patient movement, exposure settings including milliamperage (mA) and peak kilovoltage (kVp), and presence of high-density elements [ 5 , 8 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Without iodinated contrast, CT becomes significantly limited because of low inherent contrast between different types of soft tissues [ 19 ]. Adjusting the window width and level settings, aka “windowing,” is a process used to adjust the grey tones in CT images during their visualization, with the aim to adjust window width and level for optimum tissue contrast for lesion detection [ 20 ]. Different areas of anatomy or organ systems are interpreted using different window level and width settings, and generally accepted default settings are available for examination [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the implant diameter was overestimated for almost all images acquired with the small-FOV standard protocol. This increase may be related to some factors, such as spatial resolution (i.e., partial volume effect and other sources of blurring), contrast resolution (e.g., histogram distribution), filter and cut-off value used during reconstruction, beam hardening, and photon starvation [3,4,12]. Also, when comparing the medium FOV with small-FOV protocols at standard resolution, in a few cases, the medium FOV performed better and this can be possibly attributed to the reduced interference from the exomass, which are the structures located outside of the FOV but still between the X-ray source and the receptor [18].…”
Section: Discussionmentioning
confidence: 99%
“…Because the delineation between a dental implant and the surrounding bone may be faded, previous studies have demonstrated the positive influence of image brightness and contrast (B&C) adjustments on the dimensional representation of different high-density materials [11,12]; the visualization of such adjustments may vary amongst CBCT devices, depending on the severity of the artefact and the effective contrast resolution.…”
Section: Introductionmentioning
confidence: 99%